Legal Analysis Of Death Certificate Determination Through The District Court In The Perspective Of Population Administration (Decision Study No. 407 / Pdt.P / 2025 / PN Bks) - Sitompul, Ariman (Legalpreneur Journal, 2025)
This study aims to analyze the legal basis and consideration of judges in determining the application for the issuance of death certificates through the Bekasi District Court in Decision No. 407/Pdt.P / 2025 / PN Bks. This application was submitted by Sri Haryati as the wife of the late Bambang Sarwono Hadi who died in 1995 but was never registered with the Department of Population and Civil Registration (Disdukcapil). Because of the delay in reporting, the applicant must take the path of court determination in accordance with the provisions of Article 44 of Law Number 24 of 2013 concerning Population Administration and the Circular Letter of the Directorate General of Dukcapil number 472.12/932/DUKCAPIL of 2018. The research method used is normative juridical approach, by examining the legislation and analyzing the legal facts in the decision. The results showed that the judge took into account the formal and material aspects of the application by confirming the citizen's right to a document of residence. This ruling affirms the role of the court as a corrective instrument against the negligence of the population administration that has not been reported for a long time.